Possibilidades e categorias de exploração tímbrica: considerações sobre as relações intérprete-instrumento na performance - Labrada, Leonardo Bertolini [UNESP] (2014)
The general objective of this research is to describe considerations on the performer/instrument relationship, having as a maingoal to establish categories of timbrical exploration that can encompass the sonic possibilities intrinsic to percussion instruments. On of them was chosen to be addressed in the research:the vibraphone, for being very versatile and highly sought for works and experiments on timbre. The categories were outlined by seeking commonalities between the various relationships of performer/instrument that can happen during a determined musical performance. Thepaper presents a discussion of the term extended technique, reflecting on its implications, the many views onthe issue and proposing the use of the term timbrical explorationas an alternative. Other ways to approach the soundgesture system that involves the performance are also discussed, presented by Luk Vaes and Ellen Fallowfield. At the same time, an activity with composers was developed, in which solos pieces were commissioned especially for the project, stimulating new explorations on the vibraphone through collaborative relationships.These new works for vibraphone, together with the already existing solo and chamber music repertoire for the instrument (composed from the 1950s to the present), will be used to illustrate, outline and discuss the categories of timbrical exploration, which have the purpose to serve as an interface to composers who want to work the sonic possibilities of the instrument in their compositions